Fiscal Policy, Inflation and the Accumulation of Risky Capital - Eaton, Jonathan (Review of Economic Studies, 1981)
Journal Article Fiscal Policy, Inflation and the Accumulation of Risky Capital Get access Jonathan Eaton Jonathan Eaton Princeton University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 3, July 1981, Pages 435–445, https://doi.org/10.2307/2297156 Published: 01 July 1981 Article history Received: 01 December 1977 Accepted: 01 October 1980 Published: 01 July 1981